Cariogenicity of selected commercially prepared snack beverages - Agustin, Cecille P.; de la Paz, Margarita (1983., 1983)
Feeding experiments were conducted to determine the caries-producing effect of a carbonated cola drink and a carton-packaged orange drink on the molars of rats. A total of 36 rats equally distributed according to sex were studied in 3 batches, each divided into 3 treatment groups and fed respective diets consisting of a basal diet and a test beverage of either cola drink, orange drink or deionized distilled water which served as the control. Feeding was done for 30 and 45 days after which the rats were sacrificed, processed and examined for caries lesions by gross visual evaluation and microscopic examination. Results showed that both cola drink and orange drink can produce caries in rats. Gross visual examination showed that orange drink was significantly more cariogenic than cola drink in terms of number of carious teeth produced and severity of carious lesions. No pattern of caries activity could be associated with each test beverage. Carries occurred at various sites and locations. Microscopic examination of decalcified sections of the teeth to establish depth of penetration of carious process through enamel, dentin and pulp showed higher severity scores in favor of orange drink. Differences in cariogenecity can be explained in terms of differences in caries-producing components of the test drinks.
Thesis (M.S. Foods and Nutrition)--University of the Philippines Diliman
Keywords: Beverages -- Cariogenicity of